(untitled) (Journal of Sciences & Technology, 2017)
Drying food in the sun is a safe, easy and economical way to preserve food, especially fruits. Cabinet dryers are the most popular equipment for fruit drying. Because of intermittent nature of solar energy, storage is required for uninterrupted supply in order to match the needs. The main objective of this study is to assess effectiveness of continuous solar dryer integrated with packed bed as thermal storage with natural airflow for drying figs (Ficuscarica). The cabinet dryer were envisaged theoretically (computational fluid dynamics (CFD). The distribution of the velocity and temperature of air within the solar dryer were presented during one day of August and under the climate conditions of Tlemcen (Algeria). The effects of presence of a packed bed on the distribution of velocity and temperature of airflow and on the temperature of figs were analyzed. The results show that the solar dryer design, incorporating a packed bed enhances the capabilities and performance of the solar dryer, through increasing time of drying.